Motivation of Dutch high school students from various backgrounds for applying to study medicine: a qualitative study. Issue 5 (2nd June 2017) - Wouters, Anouk; Croiset, Gerda; Isik, Ulviye; Kusurkar, Rashmi A
Abstract : Objective: To explore high school students' motivation for applying to study medicine and the factors that influence this. To find explanations for under-representation of minority students in medical education, descriptions of motivation of students with different background characteristics were compared. Design: Qualitative phenomenological study using semistructured one-on-one interviews. Setting: One predominantly white and one mixed high school in a large multicultural city in the Netherlands. The study was conducted in March–December 2015. Participants: Twenty-four high school students, purposively sampled for demographic characteristics. Methods: The analysis consisted of the coding of data using a template based on the motivation types (autonomous and controlled motivation) described by self-determination theory and open coding for factors that influence motivation. Results: The main reasons for pursuing a medical career pertained to autonomous motivation (interest in science and helping people), but controlled motivation (eg, parental pressure, prestige) was also mentioned. Experiences with healthcare and patients positively influenced students' autonomous motivation and served as a reality check for students' expectations. Having to go through a selection process was an important demotivating factor, but did not prevent most students from applying. Having medical professionals in their network also sparked students' interest, while facilitating easier access to healthcare experiences. Conclusions: The findings showed a complex interplay between healthcare experiences, growing up in a medical family, selection processes and motivation. Healthcare experiences, often one of the selection criteria, help students to form autonomous motivation for studying medicine. However, such experiences as well as support in the selection process seem unequally accessible to students. As a result, under-represented students' motivation decreases. Medical schools should be aware of this and could create opportunities to acquire healthcare experiences. High schools could incorporate internships as part of their study counselling programmes and offer tailor-made guidance to each individual student.